Denosumab effects on serum levels of the bone morphogenetic proteins antagonist noggin in patients with transfusion-dependent thalassemia and osteoporosis. Issue 1 (1st January 2019) - Voskaridou, Ersi; Ntanasis-Stathopoulos, Ioannis; Christoulas, Dimitrios; Sonnleitner, Linda; Papaefstathiou, Athanasios; Dimopoulou, Maria; Missbichler, Albert; Kanellias, Nikolaos; Repa, Konstantina; Papatheodorou, Athanasios; Peppa, Melpomeni; Hawa, Gerhard; et al.
ABSTRACT: Introduction: Noggin is an antagonist of bone morphogenetic proteins (BMPs) and has a strong effect on osteogenesis. Osteoporosis is a common complication of transfusion dependent beta-thalassemia (TDT) and denosumab has been recently emerged as a promising therapeutic option. This was a post hoc investigation of serum noggin levels among TDT patients with osteoporosis who participated in a randomized, placebo-control, phase 2b study. Methods: Patients received either 60 mg denosumab ( n = 32) or placebo ( n = 31) every 6 months for 12 months. Noggin was measured, for the first time in thalassemia patients, at baseline and at 12 months, using a recently developed high sensitivity fluorescent immunoassay. Results: Both groups showed a significant increase in noggin serum levels (denosumab p < 0.001; placebo p < 0.0001). Interestingly, the increase was higher in the placebo group. Furthermore, we observed a strong correlation between noggin and wrist bone mineral density ( r = −0.641, p = 0.002) only in the denosumab group. Conclusion: In conclusion, higher noggin levels reflected more BMP inhibition, since our assay detects free bioactive noggin, which in turn impaired bone formation in placebo group. Therefore, denosumab possibly regulates noggin and favours bone turnover in TDT patients with osteoporosis through a novel mechanism of action. Trial registration: ClinicalTrials.gov identifier: NCT02559648.